Skin Prick Test Profile: A Retrospective Study - Nopriyati Nopriyati; Cayadi Sidarta Antonius; H. M. Athuf Thaha; Sarah Diba; Yuli Kurniawati; Fifa Argentina (Faculty of Medicine, Universitas Airlangga, 2022)
Background: A skin prick test is one method to detect allergies. Skin prick testing in dermatology can be performed on atopic dermatitis and urticaria. Skin prick test can be done easily, it’s relatively safe, fast, and can use many allergens simultaneously in one test. Purpose: To describe the characteristics of the skin prick test results at the clinic of Dermatology and Venereology, Mohammad Hoesin Palembang General Hospital, for the period 2016-2021. Methods: Descriptive retrospective study using a cross-sectional approach. Medical record data for the period January 2016-December 2021. Result: The number of patients who underwent skin prick testing during the period January 2016 to December 2021 was 116 patients, dominated by women (59.5%) and those aged 26-35 years (40.5%). The majority of diagnoses examined were atopic dermatitis (48.3%) and chronic urticaria (31.9%). The most positive results were for allergens in the form of house dust mites, shrimp, and crabs. The positive proportion of milkfish allergen was higher in women, while the positive proportion of shrimp allergen was higher in men. Chicken feather allergen showed significant differences between the diagnoses of atopic dermatitis, chronic urticaria and acute urticaria. Conclusion: House dust mites were the dominant allergen in patients with atopic dermatitis, chronic urticaria, and acute urticaria. skin prick test is recommended to be performed in the management of atopic dermatitis, chronic urticaria, and acute urticaria in order to detect the allergen because it has signiﬁcant clinical relevance.